The complexity of condensed tannin binding to bovine serum albumin – An isothermal titration calorimetry study - Kilmister, Rachel L.; Faulkner, Peta; Downey, Mark O.; Darby, Samuel J.; Falconer, Robert J. (Food chemistry, 2016)
•The link between tannin size, protein binding and precipitation is explained.•The cooperativity hypothesis used to explain the titration curve is challenged.•The thermodynamics of proanthocyanidin binding to protein is studied in depth. Isothermal titration calorimetry was applied to study the binding of purified proanthocyanidin oligomers to bovine serum albumin (BSA). The molecular weight of the proanthocyanidin oligomer had a major impact on its binding to BSA. The calculated change in enthalpy (ΔH) and association constant (Ka) became greater as the oligomer size increased then plateaued at the heptameric oligomer. These results support a model for precipitation of proteins by proanthocyanidin where increased oligomer size enhanced the opportunity for cross linkages between proteins ultimately forming sediment-able complexes. The authors suggest tannin binding to proteins is opportunistic and involves multiple sites, each with a different Ka and ΔH of binding. The ΔH of binding comprises both an endothermic hydrophobic interaction and exothermic hydrogen bond component. This suggests the calculated entropy value (ΔS) for tannin–protein interactions is subject to a systematic error and should be interpreted with caution.